EFFECT OF NANOFLUID/POROUS MEDIA VOLUME RATIO AND ROTATING CYLINDER ANGULAR VELOCITY ON MIXED CONVECTION FLUID FLOW INSIDE A SQUARE CAVITY WITH A WAVY BASE WALL HEAT SOURCE (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
In this study, a two-dimensional numerical method is employed to discretize the governing equations for heat transfer and mixed convection inside a square cavity with a sinusoidal bottom wall. The numerical method is based on the variational formulation/finite element with triangular nonsymmetrical elements. The vertical walls of the cavity are kept at a constant cold temperature, while the constant temperature heat source is applied to the sinusoidal bottom wall. The top wall and the rotating cylinder inside the cavity are considered insulated. The dimensionless angular velocities of an insulated rotating solid cylinder that have been considered are 0, 3000, and 6000 clockwise/counterclockwise. The working fluid is Al2O3 nanofluids with porous media at varying ratios. This analysis examined various ratios of nanofluids/porous media (nanoporous) volumes to the total enclosure volume, ranging from 0% to 100%, with a 25% increment. The effect of nanoporous media volume on the main pertinent parameters (velocity vector, heatlines, isotherms, dimensionless entropy, Bejan number, streamlines, and Nusselt numbers) is investigated at various solid cylinders’ rotational angular velocities. A constant Rayleigh number (104), Darcy number (10-3), and nanopartical solid volume fraction (0.02) are used. The results of the present work have been validated against several published works, to test the accuracy of the present analysis. In the present analysis, the data is plotted for different main parameters. The findings of this work showed that the average Nusselt number values on the hot wall increase as angular velocity increases, regardless of the rotational direction. Additionally, increasing the ratio of porous media/enclosure volume above 75% does not significantly impact the Nusselt number.